PENGEMBANGAN LKS BIOLOGI SMA SUB BAB PLANTAE BERBASIS HASIL IDENTIFIKASI MORFOLOGI DAUN DI LINGKUNGAN SEKOLAH - Evie Rif'atun Nadhiroh; Imas Cintamulya (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2018)
The development of science and technology encourages the development in the aspect of education including learning resources. Learning resources should be developed in accordance with the needs of students and curriculum that apply the curriculum 2013. LKS as a source of learning should contain a summary of material and some student activities in learning, but in reality LKS used today is not qualified (valid, practical, and effective) . The number of plants that grow in the school environment encourages the development of LKS, by identifying plants in particular leaves can be used as a material for the development of LKS, especially sub chapter based Plantae leaf morphology identification into LKS more qualified. This research is aimed to develop LKS Plantae based on leaf morphology to be valid, practical, and effective. This research is a research development with R & D method (Research and Development), and use model development of ADDIE (Analyze, Design, Development, Implementation, Evaluation). LKS results of development will be measured validity, practicality, and effectiveness. Kevalidan is measured using instruments by experts, practicality is measured based on student activities during LKS use, effectiveness measured by improvements in learning outcomes and student responses. Validation results have been declared valid by experts with 79.17% percentage, the observation result of practicality get percentage of average 70% with practical criteria, student response result gets percentage average 98,5% with criterion very effective, result learn learn got 98% percentage and N-gain analysis result is 0.69 with medium criterion. So LKS is declared worthy as a teaching material for students.Keywords: LKS, Plantae, valid, practical, effective